Effectiveness of a sport-specific exercise programme for overhead athletes with unilateral subacromial shoulder pain: a study protocol of a randomised controlled trial - Guérineau, F.; Almazán-Polo, J.; González-de-la-Flor, Á. (BMJ Open Sport & Exercise Medicine, 2025)
Subacromial shoulder pain is one of the most common musculoskeletal conditions affecting overhead athletes, particularly those engaged in high-intensity training modalities such as CrossFit. The prevalence of shoulder injuries in this population continues to rise due to increased participation, repetitive overhead movements, and biomechanical stress on the rotator cuff and scapular stabilisers. While various rehabilitation approaches exist, no consensus exists on the most effective exercise intervention for improving shoulder function and pain outcomes in athletes with subacromial shoulder pain.